Caracterización de un microsensor por espectroscopia electroquímica de impedancia - Prado Olivarez, J.; Padilla Medina, J. A.; Díaz Carmona, J.; Nadi, M. (Revista Mexicana de Ingenieria Biomedica, 2007)
This paper proposed measuring method to obtain electrical properties of a dissolution properties based on electrochemical impedance spectroscopy (EIS) measurement using a micrometric dimension sensor. Polarization impedance effects on the measurement are also reported. The used measurement frequency range is 100 Hz to 1MHz, with a serum temperature of 37 ± 0.5°C and the measurements were made using a commercial LRC meter. A level voltage of 25 mV was applied to the microsensor, which is a matrix of platinum microelectrodes, having application in electrical impedance tomography (EIT). The microelectrodes dimensions are 100 µm x 100 µm and a thickness of 180 nm. The microsensor characteristics were obtained from a potassium chloride solution, which electrical properties are well known. In order to compare the obtained experimentation data a numeric simulation of the microsensor theorical model was carried out, based on the finite element method (FEM). According to measurement results obtained with the proposed measuring method electrical properties values tendency reported in other researches, at higher frequencies than 10 KHz, were confirmed, specifically for electrical conductivity.